IMPLEMENTASI METODE SOROGAN DALAM MENGATASI KESULITAN MEMAHAMI KITAB MUKHTASHOR JIDDAN BAGI SANTRI DI ASRAMA O PONDOK PESANTREN NGALAH - Reni Nur Avita Sari; Achmad Mubarok (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research is based on the application of the Sorogan Method to overcome learning boredom and difficulties understanding the Mukhtashor Jiddan book among students at the O Boarding School of Ngalah Islamic Boarding School. This research was conducted because many students often experience difficulties understanding the material, leading to boredom in the teaching and learning process. The purpose of this study was to determine how the Sorogan Method can be applied to overcome learning boredom and students' difficulties in understanding the Mukhtashor Jiddan book. The research method used was descriptive qualitative. The subjects were the boarding school leader, religious teachers (ustad/ustazah), and students. Data collection techniques in this study included observation, interviews, and documentation. The data analysis techniques used in this study included data reduction, data presentation, and drawing conclusions. The results of this study are the implementation of the Sorogan method in overcoming boredom in learning and difficulty understanding the Mukhtashor Jiddan book for students in the O dormitory of the Ngalah Islamic Boarding School. This is done by students coming forward one by one to read the material they have learned to the female teacher. Students come forward by reading the Mukhtashor Jiddan book which is bald or without harokat, reading the I'rob and briefly explaining the meaning of the material that has been read. There are several students who have difficulty understanding the information in the book. The occurrence of students who have difficulty in understanding the book has an impact on the state of students who experience boredom in learning. In this study, Ustadzah Sorogan Asrama O used mind mapping as a medium in delivering material to students who had difficulty understanding the Mukhtashor Jiddan book. There are several factors that support and hinder the implementation of the Sorogan method. However, it should be noted that despite the factors that hinder the implementation of the Sorogan method, the Sorogan method is quite effective in overcoming students who feel bored in learning, due to the difficulty in understanding the material of the Mukhtashor Jiddan book. Keywords: Sorogan Method, Learning Difficulties, Mind Mapping